2014
DOI: 10.1111/cpf.12213
|View full text |Cite
|
Sign up to set email alerts
|

The impact of predive exercise on repetitive SCUBA diving

Abstract: Both groups experienced a significant decrease in MPs at all measurements in the second series of dives compared to the first, regardless of the placement of exercise. Whether this is related to an effect of suppression of MPs or exercise timing is not clear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
6
1
Order By: Relevance
“…The variability within our pre-dive data is comparable to that observed in human populations studied for reasons other than diving, and similar to results observed in divers without DCS 22,2830 . However, it is greater than we have observed in several prior investigations 6,7,10,31,32 . A recent study reported that the blood transcriptome indicative of apoptotic, inflammatory, and innate immune responses in non-divers differed from experienced divers, even though they had abstained from diving for over 2 weeks 33 .…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…The variability within our pre-dive data is comparable to that observed in human populations studied for reasons other than diving, and similar to results observed in divers without DCS 22,2830 . However, it is greater than we have observed in several prior investigations 6,7,10,31,32 . A recent study reported that the blood transcriptome indicative of apoptotic, inflammatory, and innate immune responses in non-divers differed from experienced divers, even though they had abstained from diving for over 2 weeks 33 .…”
Section: Discussioncontrasting
confidence: 67%
“…MPs may serve as a nidus for the vascular gas emboli that are routinely seen in divers 1214 . Some have reported a close association between MPs and bubbles, while others have not 710,31 . Whether MPs are the nucleation site for bubbles, or these are parallel events, remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to venous and arterial gas emboli, the aforementioned diving-related stress factors can lead to pathophysiological consequences such as hyperoxia-induced oxidative stress (182), impaired endothelial function (202), damaged endothelial integrity with shedding of microparticles (272), and platelet and neutrophil activation promoting inflammation (273)(274)(275)320). Depending on the severity of the diving stress, these alterations can last from hours to days (169,202,273). Other than peripheral endothelial damage, markers of blood-brain barrier damage and elevations in intracranial blood flow velocities have also been demonstrated following SCUBA diving, suggesting that oxidative stress and gas emboli can harm the cerebral circulation as well (17,31).…”
Section: Diving (Decompression Sickness)mentioning
confidence: 99%
“…For example, the impact of temperature, pressure, increased work of breathing, hyperoxia and psychological stress all have detrimental physiological consequences [22,25,35,42]. Following single or repetitive dives, impairment has been reported in systemic endothelial function [8,26,31], as well as cardiac and autonomic function [5,10,15]. Depending on the severity of the diving stress these alterations can last from hours up to even a few days [35] and are brought about by a range of factors like hyperoxia induced oxidative stress, venous (VGE) and arterial gas emboli (AGE) and impaired endothelial integrity with shedding of microparticles [44].…”
mentioning
confidence: 99%